Analisis Efektivitas Pelayanan Administrasi Sebelum Dan Sesudah Implementasi Aplikasi PUSAKA Di Kantor Kementrian Agama Kabupaten Mamuju - Dimas Adi Nugraha; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
This study aims to analyze the effectiveness of administrative services at the Mamuju District Ministry of Religious Affairs Office before and after the implementation of the Pusaka Super Apps application as part of the digital transformation of public services. The method used in this study is comparative analysis with a qualitative descriptive approach, through document studies, community satisfaction survey data, and a review of policies and administrative service practices in the field. The results of the analysis show that before digitalization, administrative services were still dominated by manual systems that tended to be slow, lacked transparency, and depended on the physical presence of applicants. After the implementation of the Pusaka Super Apps since early 2023, there has been a significant improvement in service speed, transparency of procedures and costs, integrity of the apparatus, and ease of access to services for the community. This is reflected in the increase in the Community Satisfaction Index, which has reached the excellent category. However, the effectiveness of digital services still faces obstacles in the form of limited internet network infrastructure in a number of areas and differences in digital literacy levels, both among officials and the public. Therefore, strengthening infrastructure, increasing human resource capacity, and providing ongoing assistance are among the factors that are very important for maintaining the sustainability and equitable quality of digital-based administrative services in Mamuju Regency.